Effects of recognition versus disclosure of finance leases on audit fees and costs: Evidence from Japan. Issue 1 (April 2019) - Kusano, Masaki; Sakuma, Yoshihiro
Abstract: We examine the effects of recognized versus disclosed lease arrangements in the Japanese audit market. In particular, we investigate whether the relations between recognized versus disclosed finance leases and audit fees and costs are different and whether these relations differ between audit fees and costs. By employing the unique setting in which firms have both recognized and disclosed finance leases, we find that recognized finance leases are associated with audit fees, while disclosed finance leases have no such relationship. Moreover, the associations between recognized versus disclosed finance leases and audit fees are substantially different. However, neither recognized nor disclosed finance leases are associated with audit costs, and recognized and disclosed finance leases have similar associations with audit costs. Collectively, our results suggest that audit effort does not differ between recognized and disclosed finance leases and that a risk premium is charged to recognized finance leases relative to disclosed finance leases.